Autoimmune Hepatitis: Clinical Manifestations and Diagnostic Criteria - Ian G Mcfarlane (Canadian Journal of Gastroenterology)
In 1998, the International Autoimmune Hepatitis Group - a panel of 40 hepatologists and hepatopathologists from 17 countries who have a particular interest in autoimmune hepatitis (AIH) - undertook a review, in light of subsequent experience, of the descriptive criteria and diagnostic scoring system that it had proposed in 1993 for the diagnosis of AIH. This review (published in 1999) noted that the original descriptive criteria appeared to be quite robust and required only relatively minor modifications to bring them up to date with developments and experience in diagnostic modalities for liver disease in general. Analysis of published data on the application of the original criteria in nearly 1000 patients revealed that the diagnostic scoring system had an overall diagnostic accuracy of 89.8%, with a sensitivity of 98.0%. Specificity for excluding definite AIH in patients with chronic viral hepatitis and circulating autoantibodies or patients with overlapping cholestatic syndromes was 98% to 100%, but specificity for excluding probable AIH in these disorders ranged from only 60% to 80%. Modifications, including adjustments to the weightings against biochemical and histological cholestatic features, have been made to the scoring system to improve its specificity.